Dynamic behavior of corroded RC slabs with macro-level stochastic finite element simulations. (15th July 2021) - Daneshvar, Kambiz; Moradi, Mohammad Javad; Ahmadi, Kambiz; Mahdavi, Golsa; Hariri-Ardebili, Mohammad Amin
Abstract: The reliability of reinforced concrete (RC) structures can be estimated based on the required capacity ratio. The structural demand increases with population growth and climate change, while the capacity is reduced by rebar corrosion and concrete deterioration. Several engineering structures (e.g., bridges deck and harbors) are susceptible to both corrosion and dynamic/impact loads. Therefore, the objective of this paper is to investigate the dynamic behavior of RC slabs with corroded reinforcement, and potential concrete deterioration. For this purpose, the RC slab is subjected to accelerated corrosion test using constant current technique. The corroded and sound slabs are then tested under the low-velocity impact load. A simple yet practical macro-scale finite element model is prepared which includes the concrete damage model, reduction in reinforcement diameter, and volumetric change in the rust. Global numerical responses show a satisfactory correlation with experiments, while the differences in damage pattern can be attributed to the heterogeneous deterioration in concrete and rebar. Subsequently, a large number of parametric and stochastic simulations are performed assuming different degrees of corrosion for rebars, various arrangements, non-uniform corrosion, homogeneous, and heterogeneous concrete deterioration. Results indicate that rebar corrosion, as well as concrete aging, has a crucial effect on structural capacity. Moreover, the random fields theory is an efficient technique to simulate the heterogeneity of concrete. Highlights: Dynamic behavior of reinforced concrete slabs with corroded rebar is studied. Both the experimental tests and the numerical simulations are performed. A series of parametric analyses are performed based on non-uniform rebar corrosion and concrete deterioration. Damage pattern and failure modes are identified and quantified. Results are presented in terms of acceleration, displacement, force, stiffness, and energy dissipation.